Development of Manganese Carbonyl Loaded Upconversion Nanoparticles for Near‐Infrared‐Triggered Carbon Monoxide and Mn2+ Delivery - Yile Zheng; Yi Wei; Yuying Yang; Xiang Wen; Cai Yang; Yating Xiao; Zhen Du; Xiangsheng Liu (Advanced NanoBiomed Research, 2024)
Photoactivatable carbon monoxide‐releasing molecules (CORMs), typically based on transition‐metal carbonyl complexes, have reliance on activation by UV or visible light that restricts their biomedical applications. To address this limitation, a near‐infrared (NIR)‐responsive nanoplatform is presented based on upconversion nanoparticles (UCNPs) loading with manganese carbonyl complex Mn2(CO)10 that concurrently releases CO and manganese ion (Mn2+). With the UCNPs, the more tissue‐penetrable NIR is used to locally generate UV light for photodecomposition of Mn2(CO)10 into CO and manganese oxide (MnOX), after which MnOX is reduced to Mn2+ by the overexpressed glutathione in cancer cells. Moreover, the released Mn2+ can serve as a magnetic resonance imaging contrast agent to monitor the NIR‐controlled corelease of CO and Mn2+ in real time. Therefore, this nanoplatform can provide a potential strategy for NIR‐enabled spatiotemporally release of CO and Mn2+, enhancing the controlled delivery and biomedical application of CORMs.